PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS GOOGLE SITES BERORIENTASI MODEL PEMBELAJARAN FIVES UNTUK MENINGKATKAN MOTIVASI DAN KEMAMPUAN NUMERASI PESERTA DIDIK KELAS V SD - Ning Listiarini, Dian; Rasmitadila; Dewi Nirmala, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low numeracy skills of students at the Elementary School level, based on the results of the National Assessment, show that around 38% of fifth grade elementary school students are in the "need special intervention" category in numeracy. Based on the results of a preliminary study on the SDN Cidokom 02 Education Report released on March 18, 2025, there was a decrease of 20.20% compared to 2024 in the numeracy indicator. In addition, the results of classroom observations showed a decrease in numeracy indicators and low motivation to learn mathematics due to learning that tends to be conventional, and has not been optimal in utilizing interactive digital media. This study aims to develop digital teaching materials based on Google Sites oriented to the FIVES learning model to improve learning motivation and numeracy skills of fifth grade students at SDN Cidokom 02. The research method used is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were 41 fifth-grade students of SDN Cidokom 02. Data collection was conducted through questionnaires and tests. The validation results of the Google Sites-based digital teaching materials oriented to the FIVES learning model showed an average feasibility score of 93.9%, categorized as very feasible for use. The product's practicality was evidenced by an average observation score of 3.48 and a positive student response of 87.02%. The effectiveness of the teaching materials was proven by an increase in the average motivation and numeracy scores of students from a pretest of 51.71 to a posttest of 82.93, as well as an N-Gain value of 0.6488, which is considered quite effective. These findings indicate that Google Sites-based digital teaching materials with the FIVES model are able to significantly improve learning motivation and numeracy skills